Study of cryopreserved placental cells biological effect on organotypic uterine culture - Mykhalchuk, Tetiana; Shevchenko, Mariia; Prokopiuk, Volodymyr; Prokopiuk, Olga (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):307